Evolution of a major extensional boundary fault system during multi-phase rifting in the Songkhla Basin, Gulf of Thailand. (1st April 2019) - Phoosongsee, Jidapa; Morley, Christopher K.
Graphical abstract: Highlights: Songkhla basin has four phases of tectonic activity. Eocene – boundary faults conformed to a coherent fault model. Oligocene – Miocene – boundary faults switched to an isolated fault model. Abstract: The Cenozoic N-S trending Songkhla rift basin, located in the southwest Gulf of Thailand, is a half-graben structure. The boundary fault zone on the western side of the basin is formed from a series of N-S to NNE-SSW, east-dipping normal faults. The Songkhla basin is an example of a predominantly orthogonal extended half graben that developed in phases between the Late Eocene and the early Middle Miocene, and appears to be little affected by pre-existing fabrics. The rift spans two phases of rifting: the Eocene-Oligocene phase that is present in the eastern, and the Oligocene-Miocene phase that is present in the western Gulf of Thailand and onshore areas. 2D and 3D seismic data shows that the tectonic phases within the Songkhla basin are slightly different from the overall regional pattern and comprises: (1) an early rift stage in the Eocene; (2) a late rift stage from Oligocene to Early Miocene (3) a post-rift Middle Miocene stage, possibly with minor inversion; and, (4) continuation of post-rift subsidence from the Pliocene to recent. The early rift stage is marked by numerous relatively small extensional faults. Many of these faults became inactive during the later extensional episodes, when extension was focused on the boundary fault system. The region of the boundary fault investigated here is composed of five large segments (F1-F5). During the Eocene, the segments, except for F5, became hard linked, and generally by the end of the Eocene, throw conformed to a coherent model. However, despite the boundary fault segments becoming linked during the Oligocene to Miocene, where extensional throws were relatively low, the throw patterns along the fault zone started to change to an isolated fault model, where several throw highs and lows are present along the fault trace.